Feed Intake in Guinea Fowl, Layer Hen and Pheasant as Influenced by Particle Size of Pelleted Diets* - Tufarelli, V.; Khan, R.U.; Laudadio, V. (International Journal of Poultry Science, 2011)
This study investigated the effect of pelleted diets prepared differing by levels of grinding preparation (2 or 4 mm) to evaluate pellet quality and diet preferences in adult breeders poultry species: guinea fowl (Numida meleagris), layer hen (Gallus domesticus) and pheasant (Phasianus colchicus) to improve our understanding of the diet physical structure influencing feed intake. All diets were of identical composition as well as same environment and management were provided for all treatments. The parameters evaluated in this 4 weeks feeding trial included: live body weight, feed intake, feed efficiency and pellet durability index. Body weight gain, feed intake and feed efficiency were influenced (p<0.05) by the dietary treatments in each poultry species. The present data suggest that pellet particle size is advantageous in terms of feed intake and efficiency in poultry.